Small business for dummies - Tyson, Eric; Schell, Jim (John Wiley & Sons, Inc., 2018)
The leading resource for starting and running any small business. Want to start the small business of your dreams? Want to breathe new life into the one you already have? Small Business For Dummies provides authoritative guidance on every aspect of starting and growing your business, from financing and budgeting to marketing, management and beyond. This completely practical, no-nonsense guide gives you expert advice on everything from generating ideas and locating start-up money to hiring the right people, balancing the books, and planning for growth.
Includes index. - Online resource; title from PDF title page (EBSCO, viewed July 12, 2018)
Keywords: Small business -- Management; Petites et moyennes entreprises; Gestion; BUSINESS & ECONOMICS; Small Business; Small business; Management